PENGARUH BERBAGAI NILAI EC (ELECTRICAL CONDUCTIVITY) TERHADAP PERTUMBUHAN DAN HASIL BAYAM (AMARANTHUS SP.) PADA HIDROPONIK SISTEM RAKIT APUNG (FLOATING HYDROPONICS SYSTEM) - M. Subandi; Nella Purnama Salam; Budy Frasetya (JURNAL ISTEK, 2015)
Availability of land is one of the factors that can distract in farming, mostly on the horticultural plants like spinach vegetable. Spinach vegetable contained vitamin and mineral that needed by human. Hydroponic systems are technically can be used as a means of cultivating with such limitations. Hydroponics system with floating raft is able to provide nutrient elements required by plants, because roots can absorb nutrient elements anytime and positions the sub merged direct root nutrient solution. The purpose of this study was to determine the influence of various EC value (Electrical Conductivity) of the optimal fertilizer AB Mix towards growth of spinach (Amaranthus sp.). This research is held at Ciparanje, Jatinangor, Sumedang on May till June 2014. This research uses the random arrangement of a non-factorial group which have the values of EC (e1 = 1,5 mS cm-1 ; e2 = 1,8 mS cm-1 ; e3 = 2,1 mS cm-1 ; e4 = 2,4 mS cm-1 ; e5 = 2,7 mS cm-1 ; and e6 = 3,0 mS cm-1) with 4 replicates. Research results showed the level of e6 is capable of giving the best results against the height parameter, the vast index plant leaves, fresh weight, and dry weight. While on root length parameter, harvest index, and the shoot root ratio root does not significant different results for real. This is caused by nutrient solution pH which was not inaccordance with the needs of the crop of spinach with hydroponic systems. Hydroponic system on the recommended nutrient solution pH 5-6, nutrient solution pH while in the land ranged from 6-10. It became a bench mark growth of plants that were not optimal. Keywords : EC (Electrical Conductivity), Floating Hydroponics System, Spinach